Direct observation of the strange b Baryon Ξb - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahn, S. H.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; et al. (American Physical Society (APS), 2007)
We report the first direct observation of the strange b baryon Ξb-(Ξ̄b+). We reconstruct the decay Ξb-→J/ψΞ-, with J/ψ→μ+μ-, and Ξ-→Λπ-→pπ-π- in pp̄ collisions at s=1.96TeV. Using 1.3fb-1 of data collected by the D0 detector, we observe 15.2±4.4(stat)-0.4+1.9(syst) Ξb- candidates at a mass of 5.774±0.011(stat)±0.015(syst)GeV. The significance of the observed signal is 5.5σ, equivalent to a probability of 3.3×10-8 of it arising from a background fluctuation. Normalizing to the decay Λb→J/ψΛ, we measure the relative rate σ(Ξb-)×B(Ξb-→J/ψΞ-)σ(Λb) ×B(Λb→J/ψΛ)=0.28±0.09(stat)-0.08+0.09(syst). © 2007 The American Physical Society.